Cross-Infectivity of Ralstonia solanacearum from Marigold Grown in Andaman Islands - K Sakthivel (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2016)
Bacterial wilt disease, caused by Ralstonia solanacearum, is one of the major concerns for marigold cultivation in Andaman Islands. Cross-infectivity potential of the bacterial wilt pathogen, isolated from marigold, was tested in other common vegetable-hosts of the Island. Pathogen identity was confirmed by morphological identification and Biolog based phenotypic fingerprinting. Cross-infectivity tests revealed tomato to be the most susceptible among the three solanaceous hosts tested. Highest wilt incidence was observed in tomato and marigold (100%) plants, followed by 55.6% in brinjal and 22.3% in chilli, upon artificial soil inoculation. Our study enlightens pathogenic potential of the bacterial wilt pathogen in important vegetable crops of Andaman Islands and can help formulate suitable management practices for successful management of the pathogen.